Pemanfaatan Digital Marketing Bagi Pelaku UMKM di Kelurahan Malakaji Kabupaten Gowa - Muh Rizal; Andi Aslinda; Muh. Jihad Firman; Muhammad Luthfi Siraj (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. PKM activities carried out for UMKM players in Malakaji Village, Gowa Regency which aim to foster more innovative business ideas and opportunities through information obtained in online media and use social media as digital marketing to develop a business and create UMKM productivity and increase sales of local Indonesian products on the global market scene. This service activity is carried out for 6 months which is divided into three stages, namely: (1) planning stage, (2) implementation stage, (3) evaluation stage. This PKM activity uses methods in the form of skills training through lectures, demonstrations and questions and answers and the target of this PKM activity is MSME actors. The results of the implementation of this service activity can be carried out very well by using the online system (zoom), it is also shown that there is a high enthusiasm from the participants as many as 20 people who take part in the training activities and participants can also understand all the material explanations well and feel satisfied and pleased that the material matched the needs of the participants in developing their business. The supporting factors for this training can run well, there is support from the village government and the enthusiasm of UMKM players to take part in the training. While the inhibiting factor, namely the existence of the Covid-19 pandemic condition, resulted in the PKM activity process having to be carried out through an online system and the level of knowledge of some UMKM players who really did not understand the use of internet technology.